H.R. 3532, the Antarctic Environmental Protection Act : hearing before the Subcommittee on Science of the Committee on Science, Space, and Technology, U.S. House of Representatives, One Hundred Third Congress, second session, February 8, 1994. - United States. Congress. House. Committee on Science, Space, and Technology. Subcommittee on Science. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1994)
"No. 117." Mode of access: Internet. 17